Kodon-Kodon Hotel Resort With Neo Vernacular Approach - Eddy, Firman; Haris, Maulana (Talenta Publisher, 2020)
Resort hotels are usually built in tourist areas such as mountains, beaches, and lakes. The problem in this design is that contoured land becomes more difficult in designing compared to flat land. But how to create an advantage on the contoured land, and how to create a design and building in accordance with the title raised and the purpose of that is to support the existence of functions building according to the project case. The purpose of designing this Resort Hotel is to increase the number of foreign and local tourists who come to North Sumatra especially to the Lake Toba area and provide temporary shelter and recreational activities for the community and tourists who come. The method used is to apply the local wisdom of the Karo tribe. The shape of the roof at the Karo traditional house is applied to the hotel which has been designed and the use of ornaments as facades on building looks to apply the neo-vernacular architectural theme. The results of the design of Resort Hotels to attract tourists to visit this Hotel and the Hotel also aims to preserve the local wisdom of Karo tribes.